2013
DOI: 10.1371/journal.pone.0073426
|View full text |Cite
|
Sign up to set email alerts
|

Functional Cross Talk between CXCR4 and PDGFR on Glioblastoma Cells Is Essential for Migration

Abstract: Glioblastoma (GBM) is the most common and aggressive form of brain tumor, characterized by high migratory behavior and infiltration in brain parenchyma which render classic therapeutic approach ineffective. The migratory behaviour of GBM cells could be conditioned by a number of tissue- and glioma-derived cytokines and growth factors. Although the pro-migratory action of CXCL12 on GBM cells in vitro and in vivo is recognized, the molecular mechanisms involved are not clearly identified. In fact the signaling p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
26
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 29 publications
(30 citation statements)
references
References 34 publications
4
26
0
Order By: Relevance
“…CXCR4 belongs to the family of GPCRs and requires CXCL12 ligand binding for signal activation. The inhibition of CXCR4 also decreased PDGF-BB/PDGFRb-induced cell migration, which underlined the functional importance of this cross-talk (147). Moreover, there is evidence that this crosstalk is specific for PDGFR because several studies demonstrated that inhibition of EGFR activity did not influence cell Angiotensin II (AngII)-activated ATR1 interacts with Gq, a heterodimeric G protein that activates phospholipase C (PLC) and simultaneously increases the deposition of intracellular Ca 21 .…”
Section: Pdgf Cross-talk With Other Signaling Pathwaysmentioning
confidence: 97%
See 2 more Smart Citations
“…CXCR4 belongs to the family of GPCRs and requires CXCL12 ligand binding for signal activation. The inhibition of CXCR4 also decreased PDGF-BB/PDGFRb-induced cell migration, which underlined the functional importance of this cross-talk (147). Moreover, there is evidence that this crosstalk is specific for PDGFR because several studies demonstrated that inhibition of EGFR activity did not influence cell Angiotensin II (AngII)-activated ATR1 interacts with Gq, a heterodimeric G protein that activates phospholipase C (PLC) and simultaneously increases the deposition of intracellular Ca 21 .…”
Section: Pdgf Cross-talk With Other Signaling Pathwaysmentioning
confidence: 97%
“…Moreover, phosphorylation of Shc-PDGFRb by AngII was more effective than by PDGF-BB alone (146). Sciaccaluga and colleagues recently described a functional cross-talk between PDGFRb and CXCR4 signaling in human glioblastoma cells, which was essential for cell migration (147). CXCR4 belongs to the family of GPCRs and requires CXCL12 ligand binding for signal activation.…”
Section: Pdgf Cross-talk With Other Signaling Pathwaysmentioning
confidence: 99%
See 1 more Smart Citation
“…It is clear, however, that PDGF/PDGFR plays an important role in GBM progression or origin as it may induce glioma if coupled with mutations in TRP53 and PTEN (phosphatase and tensin homolog deleted on chromosome 10) [68] . Some reports have shown that PDGFR interacts with protein kinase A (PKA) to activate cell motility [73] , while another investigation highlights a crosstalk with CXCR4 to induce cell proliferation and infiltration [74] . CSCs are now attracting attention as possible targets for glioma development, and PDGFR is also reported to participate in CSC propagation and maintenance [75] .…”
Section: Platelet-derived Growth Factor (Pdgf)mentioning
confidence: 99%
“…Alternatively, many GPCRs require RTK activity to elicit a migratory response. For example, CXCR4-induced chemotaxis depends on PDGFR activation in GBM cells, as blocking the activity of either receptor reduces the chemotactic response to both ligands (Sciaccaluga et al, 2013). A similar relationship exists between FPR and EGFR (Chen et al, 2007; Huang et al, 2007).…”
Section: Gpcr Signaling To Oncogenic Pathwaysmentioning
confidence: 99%